A Study to Assess the Effectiveness of Honey in the Reduction of Constipation and Insomnia among Antenatal Mothers during the Third Trimester of Pregnancy - Hemavathi Rajagopal; Radha Kumari; Padma Priya Deenadayalan; Beautily Viyakappan (Wolters Kluwer Medknow Publications, 2024)
A quasi-experimental quantitative approach with pre and posttest design was conducted at urban public health center (UPHC). Forty antenatal mothers were recruited and were separated into two groups in experimental and control groups. In both the groups, a pretest was done by assessing the level of the constipation-by-constipation assessment tool. The experimental group were provided with honey with warm water continuously for six days in the morning and evening as the control group received routine care. Posttest was conducted on the 7th day in both groups using the same scale to assess the level of constipation and insomnia. The study result concluded that calculated independent "t" test value of t = 2.327 was found to be statistically significant at P < 0.01 level with posttest level of constipation and insomnia between the experimental and control group.